REAKTUALISASI EPISTEMOLOGI “BONDO BAHU PIKIR”: STUDI KOMPARATIF ETOS KERJA MAHASISWI-GURU PESANTREN AL IMAN PUTRI PONOROGO - Ishaqi Maulina; Muhammad Galih Rakasiwi (Jurnal Studi Pesantren, 2026)
In the era of disruption, the rise of pragmatism and materialist mindsets has significantly shifted youth orientations toward transactional careers. Conversely, Islamic boarding schools (pesantren) consistently maintain an alternative microcosm rooted in total devotion. This study aims to explore the reactualization of the local philosophy "Bondo, Bahu, Pikir, Lek Perlu Sak Nyowone Pisan" (Wealth, Physical Effort, Mind, and Life if Necessary) among university students who concurrently serve as teachers (mahasiswi-guru) at Pondok Pesantren Al Iman Putri Ponorogo, Indonesia. Utilizing a qualitative approach with a comparative case study design, data were collected through in-depth interviews with four ustadzah (teacher-students) representing the Junior High (MTs) and Senior High (MA) school levels. The findings demonstrate that this cultural philosophy functions as a powerful form of spiritual capital and a teocentric immunity system that dismantles transactional economic logic. In micro-comparative terms, the MTs level predominantly demands physical mobilization and structural discipline (bahu) due to the psychological instability of early adolescent students. Meanwhile, the MA level primarily exhausts cognitive-psychological capacities (pikir) as teachers must navigate critical Gen-Z mindsets through mentor-like guidance rather than authoritarian approaches. When facing extreme burnout from the double burden of completing university degrees at UIN Ponorogo and fulfilling intense teaching rosters, the ultimate dimension of "sak nyowone pisan" emerges as the anchor of transendental resilience. It dissolves individual ego into absolute sincerity, transforming psychological pressure into worship. This study underscores that the internalization of kiai's existential advice serves as a vital fortress for the sustainability of character-based Islamic education against modern pragmatic waves.